3D графіка та моделювання у розважальній індустрії - Рябовол, А. О. (ХНУРЕ, 2024)
The work is aimed at studying the impact and development of 3D graphics and modeling on the entertainment industry. Nowadays, almost every movie, TV series, game, and other types of entertainment contain many elements: sound design, production, special effects, and, of course, 3D graphics. 3D graphics has allowed the modern industry to create a universe of truly impressive images that become bestsellers in movie theaters, digital stores, etc. In this paper, we'll look at the development of this trend, where it is used now, besides entertainment engineering, and how it is done on the example of creating a character for a 2D project.
Keywords: 3D графіка; розважальна індустрія